A walk through life : issues and challenges through the eyes of a Muslim woman - Kassim, Norma (Kuala Lumpur, NK & Associates, 2007)
A Walk Through Life: Issues and Challenges Through the Eyes of a Muslim Woman by Norma Kassim is a reflective book that explores the personal, social, and spiritual struggles faced by a Muslim woman. Drawing from her own experiences, the author discusses topics like identity, faith, gender roles, family, and resilience. The book offers an honest and empowering perspective on how Islamic values and inner strength help overcome life$1 (Bs challenges.s